POPLINE - Johns Hopkins University. Center for Communication Programs; Information and Knowledge for Optimal Health Project (Baltimore, Md. : Johns Hopkins Bloomberg School of Public Health, Center for Communication Programs)
POPLINE, provides bibliographic citations to the worldwide literatur e on family planning technology, family planning programs and populatio n law and policy. Demography, AIDS and other sexually transmitted disea ses, maternal and child health, primary health care communication, and population and its effect on the environment are covered when related t o developing countries.
Using the Windows 95 or NT Start Menu, select Run and type in <drive>: r32e301.exe, where <drive> stands for the driv e letter you assigned to your CD-ROM drive.
Systems requirements: Acrobat reader, Windows 95, or Windows NT 3.5. 1 or later; 8Mb of free RAM (16Mb for Windows NT)
In English, French and Spanish.
Keywords: Birth control; Reproductive health; Population policy